Treatment of patients with osteoporosis: issues of therapy duration, adherence, and replacement - N. V. Toroptsova (Современная ревматология)
Osteoporosis is a chronic disease requiring long-term treatment aimed at reducing the risk of low-energy fractures, by improving the quality and strength of bones when taking this or that drug. Bisphosphonates (BPs) are deposited in the bone, so that they have an aftereffect. Due to the increased risk of adverse reactions with BPs, the author considers that the patients may take a drug holiday or be switched to alternative therapy. Denosumab may be used continuously for years and, unlike BPs, does not require discontinuation. It is effective in both untreated and already BP-treated patients. At the same time, when the treatment is discontinued, the effect of denosumab is reversible; therefore, oral BP or intravenous zoledronic acid is recommended to maintain the achieved effect.